2006
DOI: 10.1016/j.clinph.2006.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Auditory processing during deep propofol sedation and recovery from unconsciousness

Abstract: Objective: Using evoked potentials, this study investigated effects of deep propofol sedation, and effects of recovery from unconsciousness, on the processing of auditory information with stimuli suited to elicit a physical MMN, and a (music-syntactic) ERAN. Methods: Levels of sedation were assessed using the Bispectral Index (BIS) and the Modified Observer's Assessment of Alertness and Sedation Scale (MOAAS). EEG-measurements were performed during wakefulness, deep propofol sedation (MOAAS 2-3, mean BISZ68), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 40 publications
8
54
0
2
Order By: Relevance
“…The cognitive processes eliciting these brain responses are hence most likely different as well Koelsch et al, 2005;Koelsch et al, 2006;Leino et al, 2007). In particular, the extraction of rules dictating a hierarchical structure of musical events seem to require generators in the prefrontal cortex, whereas for the extraction of sequential music rules determining the frequency ratio between two consecutive sounds, the auditory cortex plays a primary role.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cognitive processes eliciting these brain responses are hence most likely different as well Koelsch et al, 2005;Koelsch et al, 2006;Leino et al, 2007). In particular, the extraction of rules dictating a hierarchical structure of musical events seem to require generators in the prefrontal cortex, whereas for the extraction of sequential music rules determining the frequency ratio between two consecutive sounds, the auditory cortex plays a primary role.…”
Section: Resultsmentioning
confidence: 99%
“…These two electrophysiological brain responses share similar temporal and scalp distributions, with amplitudes increasing with the degree of (acoustic or harmony) violation and both are linked to behavioral discrimination performance . Although the MMN seems to be more strictly automatic as it can be elicited in participants under deep sedation by anesthesia, both the MMN and the ERAN can be elicited pre-attentively (Heinke et al, 2004;Koelsch et al, 2006). In contrast to the MMN, the ERAN has peak latency and amplitude that specifically depends on the degree of harmonic appropriateness Leino et al, 2007;Steinbeis et al, 2006), which, in turn, is related to prior (implicit or explicit) knowledge of Western tonal harmony.…”
Section: Introductionmentioning
confidence: 99%
“…Given that this deviance-dependent activity may be completely absent during many call events, and thus is not strongly linked to sensory coding, and given that it is present under anesthesia, it may reflect an early-stage process that is involved in the involuntary capturing of attention. This is also a suggested function of the mechanisms that underlie the EEG recorded MMN in humans (Escera et al, 1998), which is usually recorded in awake human subjects, but has also been shown to occur under deep anesthesia (Koelsch et al, 2006) and during sleep (Sculthorpe et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…MMN is a component of negative polarity of scalp-recorded event-related potentials (ERPs) at about 150-200 ms poststimulus (Näätänen et al, 1978;Näätänen, 1990). MMNs observed even in comatose (Kane et al, 1996) and generally anesthetized (Koelsch et al, 2006) adults as well as sleeping infants (e.g., Alho et al, 1986) suggest that MMN is also reasonably independent from the awake behavioral state.…”
Section: Introductionmentioning
confidence: 99%